2016
DOI: 10.1136/archdischild-2016-310863.41
|View full text |Cite
|
Sign up to set email alerts
|

G44(P) Use of liquidised food through gastrostomy

Abstract: Objectivesand Study Children with complex needs who are gastrostomy fed are invariably prescribed commercially produced feeding diets to meet their nutritional requirements. Popularity of a blended diet in the UK is rapidly increasing with a call for better recognition.1 Current published evidence is limited and hence no support from professional bodie. It is generally believed that blended diet through gastrostomy could have the potential risks of compromising nutritional stability, possible contamination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Participants also valued the social inclusivity of having a family meal consisting of ‘normal’ foods and the ability to have control over food choices with some choosing to include or exclude specific foods for therapeutic effect. Opinions held by participants in this research are in line with other case‐based reviews with regards to parents benefitting from using family foods which, in turn, normalises feeding . Study participants all described the basis of their meals being family foods rather than adhering to specific recipes via the gastrostomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants also valued the social inclusivity of having a family meal consisting of ‘normal’ foods and the ability to have control over food choices with some choosing to include or exclude specific foods for therapeutic effect. Opinions held by participants in this research are in line with other case‐based reviews with regards to parents benefitting from using family foods which, in turn, normalises feeding . Study participants all described the basis of their meals being family foods rather than adhering to specific recipes via the gastrostomy.…”
Section: Discussionmentioning
confidence: 99%
“… also do not detail food preparation and storage practices, which can affect bacterial content of samples. Thiagesh and Hill also noted the absence of any complications including tube blockage, gastrointestinal infection or significant nutritional deficiencies. It is unclear whether there are risks associated with blended diet in the present study or if risks have been successfully mitigated, given that all participants will have completed a risk assessment as per local policy .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the scoping review discuss the clinical impact and well-being of patients using a blended diet (6,40,51) , such as the intimacy of the feeding act between a child and parent, and the importance of providing a tube-fed child with the same meal as others in the family (38) . They also explain how using blended food ensures that children who are able to have some oral intake can receive the same food by mouth as they would by gastrostomy.…”
Section: Patient Experiencementioning
confidence: 99%
“…Perceptions and reality did not always match. One study reported that, in practice, dietitians found there were (20) Evaluate different enteral formulas Careful evaluation of formulas required in conjunction with available scientific and research studies prior to routine use in clinical practice Guenter and Lyman (2016) (33) To examine benefits and challenges for Enfit â Need open dialogue between manufacturers, clinicians and patients for success Thiyagesh and Hill (2016) (51) Single case study to describe impact of BD Improved tolerance and reduction in reflux and increase weight gain Thomas (2016) (34) To develop a protocol around administering BD in schools…”
Section: Clinician Experiencementioning
confidence: 99%
“…However, there is increasing patient and carer‐led interest in providing nutrition using blended or liquidised food that is prepared and administered at home . Reported benefits associated with blended diets include improvements in reflux and bowel problems and empowering patients and carers without ‘medicalising’ feeding . A number of concerns about the health risks associated with blended diets have been described and these include nutritional inadequacy, blocked feeding tubes and food‐borne infection .…”
Section: Introductionmentioning
confidence: 99%